Characterization of alcohol consumption in university students - Luis Enrique Jiménez-Franco; Marianela Fonseca Fernández (Revista Información Científica, 2025)
Introduction: within psychopathic substances, of a legal nature with an effect on the Central Nervous System (CNS), alcohol is presented as one of the most consumed according to sociocultural characteristics.